2020
DOI: 10.1109/access.2020.2978038
|View full text |Cite
|
Sign up to set email alerts
|

A Knowledge-Based Integrated System of Hesitant Fuzzy Set, AHP and TOPSIS for Evaluating Security-Durability of Web Applications

Abstract: There has been a phenomenal increase in the use of web applications in every facet of human endeavor. From education, healthcare, banking, business to governance and so much more now depends on secure web applications. This accelerated growth in the use of web applications has led to increase in the complexity of security and hence the present day developers have to contribute more significantly towards meeting the users' requirements. However, the high security of web application is not yet efficacious enough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 26 publications
(84 reference statements)
0
69
0
1
Order By: Relevance
“…For medical device software security assessment, we have used the Fuzzy ANP-TOPSIS approach. ANP refers to the goal, criteria, and alternatives in the form of network [21,22]. The analysis of outcomes in distinct applications with the help of TOPSIS approach shows the quality assessment indicators which affect the calculating of U(x) Figure. 2 Triangular fuzzy number…”
Section: Methodsmentioning
confidence: 99%
“…For medical device software security assessment, we have used the Fuzzy ANP-TOPSIS approach. ANP refers to the goal, criteria, and alternatives in the form of network [21,22]. The analysis of outcomes in distinct applications with the help of TOPSIS approach shows the quality assessment indicators which affect the calculating of U(x) Figure. 2 Triangular fuzzy number…”
Section: Methodsmentioning
confidence: 99%
“…In 2006, authors determined that the most significant resources for context modeling are found in the ontology-based models [11]. The study listed six criteria that would be best for context modeling and these six were: richness and quality of information, distributed composition, level of formality, incompleteness, and ambiguity, partial validation and applicability to existing environments [12][13][14][15]. In addition, the study analyzed the markup scheme, key-value, logic-based, graphical, and object-oriented models.…”
Section: Proposed Methods 21 Needs and Significancementioning
confidence: 99%
“…Hence, it is significant to deliberate it in the preparation of the ontology-based context model [22]. -Security Error: Security error is a noticeable fault during the development of software that may become the cause of a future software weakness [12]. In our ontology, a software security error can be: -Design Flaw: Design flaw is an unsuitable logical judgment at the design level.…”
Section: B Production Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper covers the previous trends and attributes of malware attacks on the healthcare services and then tries to provide some significant factors with the help of experts' opinion that are affecting the healthcare organizations rapidly [16]. The article will also provide a scientific analysis of those factors through the hybrid approach of fuzzy AHP-TOPSIS methodology [17,18]. Fuzzy AHP-TOPSIS methodology is a pre-verified and old scientific multi criteria decision making technique that gives accurate as well as effective results in multi criteria decision situation [19][20][21].…”
Section: Introductionmentioning
confidence: 99%